U.S. residents’ self-reported access to veterinary care and implications for care-seeking decisions - Pasteur, Kayla; Widmar, Nicole O.; Tran, Christina V.; Croney, Candace C. (Frontiers in Veterinary Science, 2025)
IntroductionConstrained access to veterinary care may significantly affect the health and welfare of millions of pets nationwide, but little is known about how pet families’ experiences with veterinary care or their perceptions of its accessibility and quality may influence their care-seeking decisions. This study examined relationships between pet owners’ demographics, perceived access to veterinary care, and related decisions and preferences.MethodsAn online survey targeted 1,177 adults who were representative of the U.S. population in terms of sex, age, region, education, and income level. All participants provided their perceptions on ‘access to veterinary care’; only pet owners (n = 1,026) were asked about their perceptions of alternative service providers (e.g., veterinary technicians, mid-tier veterinary professionals). Similarly, only care-seekers (n = 236) were asked about their experiences with veterinarians; care-seekers who experienced barriers to care (n = 210) responded to questions regarding their willingness to seek alternative providers. Chi-square tests of independence were used to examine relationships between respondents’ demographics, perceived access to care, and preferences for veterinary service providers.ResultsOf all survey participants, most defined ‘access to care’ in terms of service provider availability (78.2%), ease of communication (77.8%), and affordability (74.7%). A majority (54.7%) of care-seekers reported distrusting their veterinarians and 36.8% reported being dissatisfied with their veterinarian’s interactions with them despite being satisfied with their pet’s care. Many pet owners believed veterinary technicians (66.7%) and mid-tier veterinary professionals (65.1%) could provide quality care equivalent to a veterinarian and preferred to seek care from them rather than forego it. Age, education, and income level were related to pet owners’ perceptions of alternative providers and care-seeking decisions. Those under 45, without an advanced degree, or earning under $100,000 + reported higher levels of agreement with statements about alternative providers, indicating more favorable perceptions.DiscussionThese findings illustrate how pet owners’ experiences while accessing care may influence their perceptions of veterinarians, satisfaction with them, and care-seeking decisions, including their willingness to seek alternative care providers. Further, they reiterate the need for solutions that enhance care-seeker access to high quality veterinary care and promote good animal health and welfare outcomes.